FACILE SYNTHESIS OF CHLORIDE-LESS ZIRCONIUM-BASED METAL-ORGANIC FRAMEWORK (MOF) AS CHROMIUM (VI) REMOVAL VIA PHOTOREDUCTION - Bahari A.M.S.; Zulkifli N.H.; Azmin A.N.; Alias N.; Rosli S.A.; Sazalli N.A.H.; Lockman Z.; Amin N.; Misran H. (Microscopy Society of Malaysia, 2023)
Zirconia based metal-organic framework (Zr-MOF) is widely known as hydrostable and thermally stable MOF structures. However, general synthesis method of Zr-MOF usually employed chloride-based materials to enhance overall crystallinity. The use of chloride-based compounds may hinder the scale-up production of Zr-MOF as it generates scheduled liquid waste and is generally corrosive. In this study, UiO-66, a Zr-MOF was successfully synthesized for the first time without using chloride ions (Cl-) at room temperature in an attempt for a green and facile synthesis. In this method, metal-organic framework formation at various metal salt (Zr2+ )-to-DMF ratio in with or without the presence of Cl- as well as its effect on relative crystallinity of UiO-66 were investigated. Decreasing the Zr2+-to-DMF ratio resulted in increased relative crystallinity (RC) regardless of Cl-. All samples exhibited X-ray diffraction peaks corresponding to (111), (002) and (022) reflection planes suggesting successful UiO-66 formation. Results obtained in this study suggested that UiO-66 with lower RC exhibited highest photoreduction efficiency of Cr (IV) at ca. 54 % in 5 ppm solution with reduction rate of 0.0028 min-1 . Higher RC value was suggested to decrease overall active sites for photoreduction reaction to occur resulting in less photoreduction efficiency. Malaysian Journal of Microscopy (2021).